Cassava root yield variability in shifting cultivation systems in the eastern Amazon region of Brazil. (7th October 2022) - Abrell, Thomas; Naudin, Krishna; Bianchi, Felix J.J.A.; Aragao, Debora Veiga; Tittonell, Pablo; Corbeels, Marc
Summary: Cassava flour is the main source of carbohydrates for family farmers in the Amazon region of Brazil. Cassava is mainly grown under shifting cultivation, in recurrent cultivation periods initiated through slash-and-burn. Its sustainability is, however, questioned due to the associated deforestation and often rapidly decreasing crop productivity. There is an urgent need to make these cassava systems more sustainable and more profitable, but we currently lack a deep understanding of the key factors governing their productivity. We conducted an on-farm study on 37 cassava fields of smallholder farmers at three locations that spanned a range of crop-fallow frequencies, some of which were initiated through slash-and-burn while others through fire-free land clearance. First, we analysed how cassava plant density at harvest was related with pedoclimatic and management factors in slash-and-burn systems. Second, we assessed the relationship between plant density and cassava root yield at harvest and conducted a yield gap analysis to better understand which factors govern cassava productivity beyond plant density in slash-and-burn systems. Finally, we compared cassava productivity between slash-and-burn and the fire-free land clearing techniques that some farmers started to adopt in the study region. Cassava yields averaged 7.2 ± 5.4 Mg ha –1 (50% of the average yield of 14.2 Mg ha –1 in the Pará State), and ranged from 0 (in case of root rot diseases) to 24 Mg ha –1 . Cassava yield was associated with plant density at harvest (ranging from 0 to 10 000 plants ha –1 ), suggesting that managing plant density is a key determinant of the attainable yield levels. In addition, differences in cassava root yields could be largely explained by differences in labour inputs for weeding and fallow clearing, the effect of the latter depending on soil texture. Therefore, our results suggest that labour is a key production factor for cassava in the shifting cultivation systems of the Eastern Amazon in which the use of external inputs, such as chemical fertilizers and herbicides, is limited. Further, root yields were influenced by the method of field preparation, whereby yields were about 50% lower (and more variable) when fields were prepared by slash-and-burn than by mechanical ploughing or herbicide application. Despite the significantly higher yields, these alternatives to burning the vegetation are, however, still hardly adopted in Paragominas. Hence, there is a need for supporting more sustainable production systems through local and national public policies. These new systems should not only focus on soil fertility management but also on weed control and, more generally, on labour productivity.